Analysis of Multiaxis Vibration Simulators - Norman Fitz-Coy (Shock and Vibration)
A mathematical procedure that quantitatively addresses issues critical to the design and operation of multiaxis vibration simulators is presented. Both kinematic and dynamic issues are considered. The analysis is applied to both 3 and 6 degrees of freedom configurations. The existence of singular configurations is mentioned and appropriate corrective measures are recommended. A methodology for determining the required actuator commands is also presented.